SOCIAL MEDIA PLATFORMS AS MULTI-SIDED STAKEHOLDERS: YOUTUBE’S ROLE IN SHAPING IMAGINARIES OF AI - Richter, Vanessa (AoIR Selected Papers of Internet Research, 2023)
Artificial intelligence (AI) is considered a key technology in contemporary societies with high amounts of resources being dedicated globally to its development. Simultaneously, AI technology has been at the center of public debate considering its societal impact. Social Media Platforms (SMPs) play a crucial role in providing a space for public debates but also partake in public discourses on various levels. Understanding social media’s power in informing, shaping, and stirring these debates as stakeholders as well as providing a public arena is crucial, especially in light of their global reach and position. While traditional media’s role is often questioned for framing public debates and resulting imaginaries, this paper is questioning what multiple roles SMPs play in shaping users and, hence, public(s) imaginaries of AI? The research design focuses on YouTube as a case study conceptualizing the platform as a multi-sided stakeholder. The operationalization is based on a mixed-method approach, considering four streams of data to analyze YouTube as an AI innovator, technological implementer, media representative, as well as a political mediator. The mixed-methods approach draws on a combination of document analysis, platform analysis as well as content analysis of YouTube content. This brings forth the ongoing negotiation between platform, creator, and users to question the multifaceted role SMPs play in shaping imaginaries of AI. The analysis showed that YouTube acts as a multisided stakeholder and is shaping users’ imaginaries of AI from various angles depending on the intended audience of the public communication, created content, or applied technology.